Performance of furniture companies: From the lens of entrepreneurial psychological capital, entrepreneurial intellectual capital, and creative innovation behavior - Mohd Yusof, Wan Zaiyana; Yahaya, Muhammad Azizi; Muhamad Tamyez, Puteri Fadzline (Penerbit Universiti Malaysia Pahang, 2023)
Furniture manufacturing is a fast-expanding global industry that is inextricably related to demography, economic performance, and global trends affecting the global population. Innovation and value-adding have slowed, while growth has been fueled by incremental inputs rather than productivity gains. This study is to determine the effects of entrepreneurial psychological capital, entrepreneurial intellectual capital, and creative innovation behavior on company performance. Questionnaires were distributed to furniture companies. The analysis was conducted quantitatively, where the findings revealed that there is a positive significant impact on entrepreneurial psychological capital, entrepreneurial intellectual capital, and creative innovation behavior. It contributes to understanding how entrepreneurial psychological capital, entrepreneurial intellectual capital, and creative innovation behavior could enhance their performance. This research presents insights into how the furniture sector can adapt to the dynamic business environment in terms of the pandemic and sustain its competitiveness.